Land Circulation, Scale Operation, and Agricultural Carbon Reduction Efficiency: Evidence from China - Haonan Song; Hui Jiang; Shiyun Zhang; Jingdong Luan (Discrete Dynamics in Nature and Society)
Based on the panel data of 30 Chinese province in 2005–2018, this paper quantifies agricultural carbon reduction efficiency (CRE), using the slack-based measure (SBM)-data envelopment analysis (DEA) model with undesired outputs (SBM-DEA∗), and empirically tests that development of land circulation market directly affects agricultural CRE, and indirectly affects agricultural CRE via scale operation of farmland. The results show that the following: (1) In the observation period, China’s agricultural CREs generally evolved from a low level to a high level, with an annual growth rate of 8.0%, but there is still a large space of carbon reduction. (2) Overall, land circulation significantly promoted agricultural CRE, but the promoting effect varied from region to region: the promoting effect was significant in eastern and central regions, and insignificant in western region. (3) Scale operation of farmland had a nonlinear, partial mediation effect on how land circulation influences agricultural CRE; land circulation greatly accelerated the scale operation of farmland, while the growing scale of farmland utilization had an inverted U-shaped influence on agricultural CRE. Our research results imply that promoting land circulation directly drives the low-carbon transformation of agriculture in China, but excessive scale operation of farmland might hinder agricultural carbon reduction.